Adenovirus and Mycoplasma pneumoniae co-infection as a risk factor for severe community-acquired pneumonia in children - Chen, Qihong; Lin, Lihua; Zhang, Ning; Yang, Yungang (Frontiers in Pediatrics, 2024)
Background: To investigate the pathogenic characteristics and risk factors of pediatric severe community-acquired pneumonia (CAP). Methods: We retrospectively analyzed the clinical data of hospitalized children with severe CAP from April 2014 to June 2019 in China. Data of age, sex and pathogenic results were collected: bacterial and fungal cultures, respiratory viruses from sputum or bronchoalveolar lavage fluid (BALF), serum Mycoplasma pneumoniae (MP)-IgM and Chlamydia Pneumoniae-IgM, and BALF or blood (1-3)-β-D-glucan/galactomannan test. Results: A total of 679 children with severe CAP were included in the analysis.The number of cases infected with MP was higher in males than in females. There were significant differences between the ≤ 1-year and > 1-year groups in terms of pathogen. The top three bacteria cultured were Haemophilus influenzae (57/679, 8.4%), Streptococcus pneumoniae (50/679, 7.4%), and Pseudomonas aeruginosa (25/679, 3.7%). The top three viruses detected were adenovirus (AdV, 124/679, 18.3%), respiratory syncytial virus (24/679, 3.5%), and parainfluenza virus (21/679, 3.1%). AdV and MP were the leading pathogens, detected in 18.3% and 32.6% cases, respectively. MP infection increased the risk of AdV infection (OR 3.77, p < 0.0001).MP infection was a risk factor for severe AdV-infected pneumonia, while sex, age, bacteria, Chlamydia Pneumoniae, fungal, and AdV infections were risk factors for severe MP-infected pneumonia. Conclusions: AdV and MP were dominant pathogens in children with severe CAP. AdV and MP infection predisposed each other to develop severe illness. AdV-MP co-infection may lead to severe pneumonia.